2013
DOI: 10.1002/jbm.a.34705
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and gene‐expressed profile in brain‐injured mice caused by exposure to titanium dioxide nanoparticles

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are widely used in toothpastes, sunscreens, and products for cosmetic purpose that the human use daily. Although the neurotoxicity induced by TiO2 NPs has been demonstrated, very little is known about the molecular mechanisms underlying the brain cognition and behavioral injury. In this study, mice were exposed to 2.5, 5, and 10 mg/kg body weight (BW) TiO2 NPs by nasal administration for 90 consecutive days, respectively, and their brains' injuries and brain gene-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 45 publications
6
93
0
1
Order By: Relevance
“…It is well known that proteins enco ding by E2F8 and USP7 genes have variable properties and can contribute to regulation of cell proliferation and apoptosis [18,25,26]. It is possible that our results can reflect the genotoxic effect of titanium nitride and chromium disilicide nanoparticles and are mostly consistent with data Ze et al [2] and Alarifi et al [8] as well as with our previous data [28,29].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By supporting
confidence: 92%
See 2 more Smart Citations
“…It is well known that proteins enco ding by E2F8 and USP7 genes have variable properties and can contribute to regulation of cell proliferation and apoptosis [18,25,26]. It is possible that our results can reflect the genotoxic effect of titanium nitride and chromium disilicide nanoparticles and are mostly consistent with data Ze et al [2] and Alarifi et al [8] as well as with our previous data [28,29].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By supporting
confidence: 92%
“…Ultrafine titanium dioxide nanoparticles is widely used in the number of applications, including white pigment in paint, ceramics, food packaging material, food additive, cosmetic creams, toothpastes, and component of surgical implants [1]. However, long-term exposure to titanium dioxide nanoparticles led to accumulation of these nanoparticles in brain, oxidative stress, over-prolife ration of all glial cells, tissue necrosis as well as hippocampal cell apoptosis, resulted in neurogenic disea se states in mice [2]. Significant changes in brain gene expressions were also founded: significant increases in collagen A1 (COL1A1), serine/threonine-protein kinase 1 (AKT1), catenin β1 (CTNNB1), cysteine and serine rich nuclear protein 1 (CSRNP1), DDIT4 (DNA Damage Inducible Transcript 4), cytochrome P450 family 2 subfamily E member 1 (CYP2E1), and Krev interaction trapped protein 1 (KRIT1) expressions and great decreases in dopamine receptor D2 (DRD2), neuraminidase 1 (NEU1), Fc receptor-like A (FCRLA), and 7-dehydrocholesterol reductase (DHCR7) expressions [2].…”
Section: We Have Studied the Effect Of Chromium Disilicide And Titanimentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that TiO 2 NPs could transfer through the BBB and thereafter induce an injury to the brain by the activation of oxidative stress responses. In another toxicity study of TiO 2 NPs in mice performed by Ze et al 71 TiO 2 NPs were translocated and accumulated in the brain through nasal administration, and this led to an oxidative stress and a series of pathological changes, such as an overproliferation of the glial cells and hippocampal cell apoptosis. The authors further noted some significant changes in genes that may be potential biomarkers of brain toxicity.…”
Section: In Vivo Studies On the Potential Toxicity Of Nanomaterials Omentioning
confidence: 99%
“…11 Moreover, a recent study showed oxidative stress in mice brain as well as overproliferation of all glial cells. 12 These occurred in mice that were exposed to 2.5 mg/kg, 5 mg/kg, and 10 mg/kg body weight TiO 2 NPs through nasal administration for 90 days. The toxicokinetics ( Figure 1) and toxic effects of TiO 2 NPs [13][14][15] alone have been well documented in many in vivo and in vitro studies, but reviews of the effects (or toxicities) of the interaction of TiO 2 NPs with other chemicals or physical factors are currently unavailable.…”
Section: Introductionmentioning
confidence: 99%